2010
DOI: 10.1016/j.yhbeh.2010.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social experience on subsequent sexual performance in naïve male Japanese quail (Coturnix japonica)

Abstract: On their first sexual encounter, naïve male Japanese quail will attend to and approach a female; they sometimes mount but they do not always copulate. During the second encounter, most males successfully copulate. Although sexual experience facilitates subsequent sexual interactions, sensory cues provided by females, independent of any sexual encounter, may also enhance sexual performance. To investigate whether previous exposure to a conspecific affects subsequent sexual behavior, we allowed inexperienced mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…Several lines of evidence indicate that this measure is indicative of the male’s motivation to approach its mate. Indeed, previous studies showed that the RCSM frequency: (1) rapidly increases in sexually active males provided with the view of a female but not when provided with a view of a male (Seiwert and Adkins-Regan, 1998; Thompson et al, 1998); (2) is readily displayed by naïve males without previous sexual learning but can also be conditioned and elicited by an arbitrary stimulus previously associated with the presentation of a sexual stimulus such as visual access to a female (Cornil et al, 2004; Holloway et al, 2005; Cornil and Ball, 2010) (3) decreases after castration but is restored after supplementation with exogenous testosterone (Balthazart et al, 1998); (4) is reduced after copulation (Schmit M., de Bournonville C. and Cornil C.A., unpublished observations) and (5) is inhibited by lesions of the preoptic area, a brain region known to control male sexual behavior (Balthazart et al, 1998). Together these observations strongly suggest that these cloacal contractions constitute a preparatory or appetitive response in anticipation of copulation that reflects the propensity of the male to engage in copulation (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Several lines of evidence indicate that this measure is indicative of the male’s motivation to approach its mate. Indeed, previous studies showed that the RCSM frequency: (1) rapidly increases in sexually active males provided with the view of a female but not when provided with a view of a male (Seiwert and Adkins-Regan, 1998; Thompson et al, 1998); (2) is readily displayed by naïve males without previous sexual learning but can also be conditioned and elicited by an arbitrary stimulus previously associated with the presentation of a sexual stimulus such as visual access to a female (Cornil et al, 2004; Holloway et al, 2005; Cornil and Ball, 2010) (3) decreases after castration but is restored after supplementation with exogenous testosterone (Balthazart et al, 1998); (4) is reduced after copulation (Schmit M., de Bournonville C. and Cornil C.A., unpublished observations) and (5) is inhibited by lesions of the preoptic area, a brain region known to control male sexual behavior (Balthazart et al, 1998). Together these observations strongly suggest that these cloacal contractions constitute a preparatory or appetitive response in anticipation of copulation that reflects the propensity of the male to engage in copulation (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…We observed for example that the RCSM frequency decreases progressively during successive tests in which the male is never provided access with the female, presumably due to a lack of sexual reinforcement (Cornil et al, 2006). This frequency is also drastically different if males have been previously exposed visually to a male or to a female (Cornil and Ball, 2010). …”
Section: Laboratory Measures Of the Anticipation Of Copulation In mentioning
confidence: 98%
“…Several lines of evidence indicate that this behavioral response reflects the sexual motivation of the male: (1) it is rapidly upregulated in sexually active males visually exposed to a female but not a male [73], (2) it is displayed by naive males but can also be conditioned to an arbitrary stimulus previously associated with the presentation of a female [74], (3) it decreases after castration but is restored by treatments with exogenous testosterone [43], and (4) is inhibited by lesions of the preoptic area, a brain region known to control male sexual behavior [43]. …”
Section: Box 1 Two Independent Controls Of Aromatase Activitymentioning
confidence: 99%